HUBUNGAN FREKUENSI PENIMBANGAN, PENGGUNAAN GARAM BERYODIUM, DAN PEMBERIAN VITAMIN A DENGAN KEJADIAN UNDERWEIGHT PADA BALITA DI PROVINSI JAWA TIMUR - Nafijah Muliah; Agus Sri Wardoyo; Trias Mahmudiono (Universitas Airlangga, 2017)
The are many causes of nutritional problems, including lack of food intake, illness, caring pattern and many other causes, one of the problems that often happen is the children had not weighed regularly. Iodine is one of the nutrients associated with the growth of children. On the other hand, children who are suffering from malnutrition usually also hasVitamin A deﬁ ciency as a result of their lack of nutrient intake. The purpose of this study was to analyze the relationship between the frequency of weighting, the use of iodized salt, and Vitamin A supplementation with underweight among children under ﬁ ve in East Java Province. This study was secondary data analysis from Monitoring of Nutritional Status (MNS) in East Java, 2016. The sample of this study were 10.440 households with children under ﬁ ve. 18.5% children under ﬁ ve in East Java were underweight, 2% overweight, and 79.5% were normal. Distribution of frequency were performed as univariate statistical analysis and the relationship between variables were analyzed by chi-square test. The odd ratio were analyze by logistic regression. There was signiﬁ cant correlation between blue-colored vitamin A supplementation (p < 0.001;OR = 0.638;95%CI:0.580-0.78w2) with underweight. However, there was no correlationbetween weighing frequency (p = 0,729) and the use of iodized salt (p = 0,620) with underweight. The conclusion of this study highlight that there was correlation between Vitamin A supplementation with underweight in East Java.